A case report of field amputation: the rescue of an entrapped patient through the "doctor car" system - Byungchul Yu; Gil Jae Lee; Min A Lee; Kang Kook Choi; Jihun Gwak; Youngeun Park; Yong-Cheol Yoon; Jayun Cho; Seung Hwan Lee; Jungnam Lee (Journal of Trauma and Injury)
In certain circumstances, invasive procedures such as creation of a surgical airway, insertion of a chest drain, intraosseous puncture, or amputation in the field are necessary. These invasive procedures can save lives. However, emergency medical service teams cannot perform such procedures according to the law in Korea. The upper arm of a 29-year-old male patient was stuck in a huge machine and the emergency medical service team could not rescue the patient. A doctor-car team was dispatched to the scene and the team performed the filed amputation to extricate the patient. He was brought to the trauma center immediately and underwent formal above-elbow amputation. Here we describe a case of field amputation to rescue a patient through a “doctor car” system, along with a literature review.